2018
DOI: 10.1177/1073191118820133
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Executive Function Weaknesses Are Linked to Elevated Internalizing Symptoms Among Community Adolescents

Abstract: Adolescence is a period of high risk for the emergence of problems with anxiety and depression. Theory and research suggest that executive function deficits accompany internalizing and externalizing problems, although more evidence is required to understand these relationships. This study employed a commonly used rating scale of executive function, the Brief Rating Inventory of Executive Function, and examined relationships with self- and parent-reported internalizing and externalizing problems among a communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 69 publications
2
16
0
4
Order By: Relevance
“…The BRIEF has been found to be best represented by models including both common and specific factors (Pérez-Salas et al, 2016; Roth et al, 2013) and has been validated in relation brain injury, developmental disabilities, and attention deficit hyperactivity disorder (Gioia et al, 2002). Data from the same study reported here found that total (Global Executive Composite) BRIEF scores were correlated with depression, anxiety, attention deficit hyperactivity disorder, and conduct disorder symptoms (Mullin et al, 2020).…”
Section: Ef/ec Questionnairessupporting
confidence: 53%
“…The BRIEF has been found to be best represented by models including both common and specific factors (Pérez-Salas et al, 2016; Roth et al, 2013) and has been validated in relation brain injury, developmental disabilities, and attention deficit hyperactivity disorder (Gioia et al, 2002). Data from the same study reported here found that total (Global Executive Composite) BRIEF scores were correlated with depression, anxiety, attention deficit hyperactivity disorder, and conduct disorder symptoms (Mullin et al, 2020).…”
Section: Ef/ec Questionnairessupporting
confidence: 53%
“…During the adolescent years, a social reorientation toward peers and gaining social acceptance coincides with a heightened risk for psychopathology including internalizing (e.g., depression and anxiety) and externalizing (e.g., impulsivity, aggression, and conduct problems) symptoms (e.g., Achenbach, 1966; Costello et al, 2011). Internalizing and externalizing symptoms involve affective dysregulation and compromised executive functioning (Kerestes et al, 2014; Mullin et al, 2018) such as poorer cognitive control (Snyder and Hankin, 2016), as measured by lower inhibitory control (Schulz et al, 2004; Vuontela et al, 2013), and altered reaction times during inhibitory failures (Albrecht et al, 2005; Ladouceur et al, 2006). This ultimately has lasting implications on adolescents’ lives (e.g., Fergusson and Woodward, 2002; Bongers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has established relationships between deficits in cognitive flexibility and verbal memory and symptoms of anxiety and depression (Iorfino et al, 2016). Mullin et al (2020) revealed a relationship between the most deficient EF skills reported by parents and the severity of anxiety and depression symptoms, as well as of externalizing symptoms. In the same line, Nelson et al (2018) concluded that early EF deficits may be an important risk factor for the development of internalizing psychopathology in childhood.…”
Section: Neuropsychological Characteristics Of Mental Disordersmentioning
confidence: 99%